2021
DOI: 10.48550/arxiv.2104.13624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Existence, uniqueness, and approximation of a fictitious domain formulation for fluid-structure interactions

Abstract: In this paper we describe a computational model for the simulation of fluid-structure interaction problems based on a fictitious domain approach. We summarize the results presented over the last years when our research evolved from the Finite Element Immersed Boundary Method (FE-IBM) to the actual Finite Element Distributed Lagrange Multiplier method (FE-DLM). We recall the well-posedness of our formulation at the continuous level in a simplified setting. We describe various time semi-discretizations that prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In [9], it was shown that a linearized version of Problem 1 admits a unique solution. See also [8] for a review on the state of the art about this problem.…”
Section: Fictitious Domain Approach: Problem Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…In [9], it was shown that a linearized version of Problem 1 admits a unique solution. See also [8] for a review on the state of the art about this problem.…”
Section: Fictitious Domain Approach: Problem Settingmentioning
confidence: 99%
“…In this setting, we are now able to state the finite element version of Problem 3 whose well-posedness has been discussed in [7] and [8].…”
Section: Finite Element Discretization Of the Stationary Problemmentioning
confidence: 99%
See 1 more Smart Citation